Managing behaviours of concern in the elderly - Boland, Michael
A high percentage of elderly people in professional care suffer from dementia, a psychiatric illness or a specific brain injury. Recently, extensive research has been undertaken into understanding the origins of behaviours of concern, focusing on addressing the variety of underlying causes. In this program we investigate defining and understanding behaviours of concern, types of behaviours and unmet needs, assessing and problem solving, possible triggers and management strategies. Systematic approaches to the identification of triggers and instigation of problem solving techniques can significantly reduce this increasingly widespread condition.